Determination of the normal reference interval for anti‐Müllerian hormone (AMH) in bitches and use of AMH as a potential predictor of litter size. (18th October 2016) - Hollinshead, FK; Walker, C; Hanlon, DW
Contents: Anti‐Müllerian hormone (AMH) is a reliable endocrine marker of ovarian reserve in many species with extensive literature in both humans and cattle. However, there are no known hormonal predictors of ovarian reserve and potential reproductive performance in the bitch. A prospective cohort study was performed involving 155 intact bitches of various ages (range 1.2–7.6 years) and breeds that were presented for routine breeding management over a one‐year period. All bitches were artificially inseminated with frozen or fresh semen using the transcervical insemination (TCI) technique. AMH concentrations were measured using a commercially available canine AMH ELISA (Ansh Labs ®, Texas, USA), which we validated prior to performing the study. The reference interval (RI) for AMH for all bitches in the study, regardless of body weight, was 2.9–21.1 ng/ml. There was a significant effect of bitch size and age on AMH concentrations. The RI for giant breeds was significantly ( p < .01) lower (1.75–15.6 ng/ml) than small‐sized (5.6–24.2 ng/ml), medium‐sized (4.3–23.7 ng/ml) and large‐sized (4.3–21.0 ng/ml) bitches. The mean AMH concentration in bitches less than 4 years of age was 12.4 ng/ml, whereas the mean AMH concentration in bitches older than 4 years of age was 10.5 ng/ml ( p < .05). For each additional year of age above 1 year of age, AMH concentrations fell by 0.5 ng/ml. There was no effect of AMH concentration on the whelping rate. Smaller breeds had smaller litters (and higher AMH concentrations), but within each breed size category, bitches with higher AMH concentrations had significantly larger litter sizes ( p < .01). For each 1 ng/ml increase in AMH, litter size increased by 0.3 pups/litter. In conclusion, we determined a normal reference interval for AMH in bitches based on body weight using a canine‐specific assay. In agreement with findings in humans and other species, we found that there is a decline in AMH concentrations with advancing age in bitches. Finally, the significant positive correlation between AMH concentrations and litter size indicates that AMH may be a useful management tool for the selection of bitches in breeding programmes.